Wealth mobility and dynamics over entire individual working life cycles - Stefan Hochguertel; Henry Ohlsson (European Central Bank (ECB), 2011)
We study taxable wealth in unique Swedish administrative data, annually following a large sample of households over a period of almost 40 years. The main data limitation is non-observability of wealth for those below the tax exemption level. This implies that much of the focus of the paper is on the rich, since we are confined to those whose wealth becomes taxable over time. We exploit the long panel dimension by estimating dynamic `fixed effects' models for limited dependent variables that allow for individual heterogeneity in both constants and autoregressive parameters, and control for heterogeneity through observables. We find substantial wealth mobility over the long time spans, partly accounted for by life-cycle behavior, while sufficiently capturing dynamics by an AR(1) process at the individual level.
Keywords: C23; D14; D31; D91; H24; 330; heterogeneity; life cycle; panel data; wealth dynamics; wealth mobility